Thyroid hormone resistance and the value of genetics: Three case reports. Issue 9 (March 2019) - Xiao, Xiao; Lv, Chen; Zhu, Tianxiao; Chen, Huiling
Abstract: Rational: Thyroid hormone resistance (RTH) is a rare disease that is characterised by a lowered sensitivity of the target organs to thyroid hormone. Herein, we present 3 cases of confirmed RTH, with the support of clinical lab results and/or gene sequencing at diagnosis. Patient concerns: The 3 included patients were found to have elevated levels of free T3 (FT3 ), free T4 (FT4 ), and non-supressed levels of thyroid stimulating hormone (TSH). Diagnosis: All patients were tested for thyroid antibodies, somatostatin suppression, vision and hearing at diagnosis. Electrocardiography (ECG), thyroid ultrasonography, and magnet resonance imaging (MRI) of the sellar region were also performed. Furthermore, gene sequencing was used to detect the thyroid hormone receptor beta (THRB) gene mutation. Interventions: Patient treatment was individualised. Patients were given levothyroxine sodium or a low dose of thyroiodin, depending on the individual symptoms. Outcomes: After treatment, thyroid function was stable in 2 of the teenage patients. No evidence of worsening thyrotoxicosis was observed. Lessons: Gene sequencing should be considered together with clinical lab results, including somatostatin suppression testing, before approaching a diagnosis of RTH.